A Aufklärung como forma de melhoramento dos costumes do gênero humano em Kant - Calovi, Gustavo Ellwanger (2018)
The present thesis tries to offer an interpretation on the question of the improvement of the customs of the human race in the horizon of the Kantian practical philosophy. In this perspective, the idea is defended that there is a textual basis in Kant to base the belief in the improvement of the human race through the articulation of two fundamental points: education and enlightenment. At first, we try to defend the idea that the Enlightenment movement has a unity and that it will directly influence the flowering of Kantian enlightened thought. Thus, it is understood that the critical use of reason added to the defense of freedom and autonomy are the fundamental elements to size the illustrated movement and that will influence Kant in the construction of his positioning before the enlightenment. In the sequence, an interpretation will be presented on the meaning of Aufklärung in Mendelssohn and Kant. Thus, it seeks to support a line of argument that indicates the relationship between enlightenment and the proposal of education advocated by Kant, given that its educational proposal is an important element within the clarification since, through it, conditions for the individual to reach autonomy. In order to systematize the discussion, in the third moment, we will present the four purposes of education thought by Kant, because it is understood that, through an appropriate pedagogical method, it becomes possible to prepare the individual to exercise his moral autonomy. Lastly, the last chapter presents the relationship between education and enlightenment and how belief in the improvement of customs can be sustained. The thesis has, on the one hand, the objective of reconstructing the Kantian argument regarding enlightenment, and, on the other hand, to demonstrate the importance of education in the search for adulthood. In this way, the idea is maintained that it is from the articulation between education and enlightenment that it is possible to defend the idea of the improvement of manners of the human race.